Cocrystal engineering of pharmaceutical solids: therapeutic potential and challenges. Issue 40 (4th October 2021) - Wong, Si Nga; Chen, Yu Chee Sonia; Xuan, Bianfei; Sun, Changquan Calvin; Chow, Shing Fung
Abstract : This highlight presents an overview of pharmaceutical cocrystal production and its potential in reviving problematic properties of drugs in different dosage forms. The challenges and future outlook of its translational development are discussed. Abstract : Cocrystals are an emerging class of crystalline materials composed of two or more different molecules in the same crystal lattice that are physically connected by non-ionic and non-covalent bonds. Formulating problematic drugs into cocrystals is a pragmatic strategy to manipulate solid state properties for new drug development and product reformulation. While research on cocrystals has been undergoing rapid growth over the past two decades, successful clinical translation of cocrystals is still limited. As the pharmaceutical properties of a cocrystal are decidedly dictated by the selection of cocrystal formers and resulting crystal structure, the present review begins with an overview of the current strategies in cocrystal design and preparation, followed by the potential applications of cocrystals in medicines. The major hurdles and missing knowledge gaps hindering the translation of pharmaceutical cocrystals into commercial reality are also mentioned. Finally, perspectives of cocrystals in alternative dosage forms other than for oral use, as well as latest topics of cocrystal research are highlighted. We believe that cocrystals play an important role in future drug discovery and development, offering a new direction for optimal drug delivery, combination therapy and personalized medicines.